New genomic regions in dry bean (Phaseolus vulgaris L.) associated with stem diameter, plant height, and other plant architecture traits - Oscar Rodríguez; Jayanta Roy; Philip E. McClean; Didier Murillo; Kristin Simons; Nusrat Khan; Jose C. Figueroa-Cerna; Juan M. Osorno (Euphytica, 2026)
Growth habit is one of the most important domestication traits in dry bean ( Phaseolus vulgaris L.). In the U.S. for example, Type II indeterminate upright plant varieties have allowed farmers to switch from historic two-pass harvest to one-pass direct harvest. Previous work suggested a stem diameter of 5.6 mm as threshold to select Type II architecture genotypes suitable for direct combining. This study aimed to validate the correlation between stem diameter and other agronomic traits using lines comprising various market classes from a public breeding program. It also assesses if stem diameter could be used to select genotypes that combine high seed yield and upright architecture. GWAS was also used to identify genomic regions related to plant height and stem diameter. Mean stem diameter among breeding lines was 7.7 mm, higher than the proposed threshold. Stem diameter showed no significant G × E interactions, with the highest broad-sense heritabilities observed for regular-darkening pinto (pinto) and slow darkening (SD) pinto. Plant height was the most relevant trait for seed yield variation in black, great northern, and navy beans. In contrast, both plant height and stem diameter are required to explain part of seed yield variability and selecting upright plants for pinto, red/pink, and SD-pinto. GWAS revealed significant regions located on chromosomes Pv03, Pv07, and Pv11 depending on trait and race used. A region near 40.7 Mb on Pv07 was associated with both plant height and stem diameter, suggesting further studies on indeterminate upright dry bean plant architecture should focus on this region.